Investigation Effect of Biorhythm on Work-Related Accidents in The Metal Industry (A Short Report) - Ehsanollah Habibi; Zahra Mohammadi; Ayoub Ghanbary Sartang; Mohammad Zeinodini (Iranian Journal of Health, Safety and Environment, 2016)
Biorhythm is one of the newest subjects in the field of cognition of mental ergonomics which can be very effective in reduction of work-related accidents or mistakes with no apparent reason. With evaluating Biorhythm individuals can intervention action to reduce job accidents carried out. Thus, the aim of this study was to determine the relationship Biorhythm and work-related accidents in the metal industry. This research is a cross-sectional and analytical-descriptive in the metal industrial Isfahan city of 120 work-related accidents during 2015. The required information was collected from available documents in HSE unit of the company biorhythm charts were drawn based on a date of accidents and participants birthdays, using natural Biorhythm Software V3.02 Conduct. Finally، the data were analyzed using spss version 20 and descriptive statistics.This study showed that the frequency of accidents in critical days and negative section of physical cycle was more than expected. Also the frequency of accidents in critical days and negative section of emotional and intellectual cycles was less than expected. Most type of injury, including cuts to 35.8 percent and the lowest type of injury was torsion with 5 percent. Most limb injury, hands and fingers with 51.7 percent and the lowest limb injury were back at 2.5 percent. Accidents outbreak in physical cycles was 38.3 percent. These 120 accidents in additionally were causing 120 loss of working days in effect accident. Most percent of loss of working days were for 20 to 30 days with of 39.2 percent. Most percent of loss of working days were for 20 to 30 days with of 39.2 percent. Due to the physical nature of the work activities in the metal industry can be stated that the study showed that in physical work activities, frequency of accidents in critical days and negative section of physical cycle in which the person is not physically ready to do the job was more than expected. Therefore, by training and increasing the knowledge of workers regarding biological cycle and its effects on mental, emotional and physical status, each person effects can make some changes to their work plans during days that they do not feel well, physically or mentally, in order to prevent the likely accidents.